2014
DOI: 10.5603/kp.a2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cardiac resynchronisation therapy in the treatment of end-stage inotrope-dependent heart failure patients

Abstract: CRT can be an alternative for end-stage inotrope-dependent HF patients with wide QRS who are ineligible for urgent heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, few studies showed a beneficial effect of CRT de novo implantation in inotropy-dependent end-stage heart failure patients. Sokal et al [7] reported 100% success in weaning from inotropes in eleven individuals after a CRT implantation. In a meta-analysis by Hernandez et al [8], weaning from inotropes was successful in 93% of patients, and the 1-year survival rate was 69% after CRT de novo implantation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies showed a beneficial effect of CRT de novo implantation in inotropy-dependent end-stage heart failure patients. Sokal et al [7] reported 100% success in weaning from inotropes in eleven individuals after a CRT implantation. In a meta-analysis by Hernandez et al [8], weaning from inotropes was successful in 93% of patients, and the 1-year survival rate was 69% after CRT de novo implantation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite these guidelines, there are reports of successful off-label de novo CRT implantations in inotropy-dependent patients or on mechanical support [7,8]. However, there are only limited data on off-label CRT upgrades [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There have been few selective studies and case reports investigating the usefulness of “rescue” CRT in patients with non-ambulatory New York Heart Association (NYHA) functional class IV HF or cardiogenic shock. 3) 4) 5) 6) 7) Most attempts, however, have been unsuccessful. For example, in a retrospective study by Mantziari et al 3) 24 patients underwent CRT implantation during hospitalization in the cardiac critical care unit.…”
Section: Discussionmentioning
confidence: 99%
“… 1) 2) However, uncertainty remains whether it is beneficial to implant CRT devices in patients with severe HF, especially those in cardiogenic shock or end-stage HF, since such patients have been excluded from most CRT trials. Few cases have been reported about CRT implantation in patients with acute decompensated HF being treated with vasopressors/inotropes, 3) 4) 5) 6) but patients in the intensive care unit requiring mechanical circulatory support were usually not considered as eligible for CRT or CRT-implantable cardioverter defibrillator (CRT-D) “salvage” therapy. In this report, we present a case of successful extracorporeal membrane oxygenation (ECMO) weaning in a cardiogenic shock patient after CRT-D implantation.…”
Section: Introductionmentioning
confidence: 99%
“…However, current guidelines do not recommend CRT in non-ambulatory NYHA class IV HF patients [2,3] . Several small, retrospective studies of CRT implantation in inotrope-dependent HF patients have described high rates of successful implant, weaning from inotrope, clinical improvement, hospital discharge, and in some cases echocardiographic improvements following CRT [10][11][12][13][14][15][16][17] . To our knowledge, no previous studies or cases have specifically described CRT implant in ventilator-dependent HF patients.…”
Section: Discussionmentioning
confidence: 99%